Identifying psychiatric disorder-associated gut microbiota using microbiota-related gene set enrichment analysis. (5th April 2019) - Cheng, Shiqiang; Han, Bei; Ding, Miao; Wen, Yan; Ma, Mei; Zhang, Lu; Qi, Xin; Cheng, Bolun; Li, Ping; Kafle, Om Prakash; Liang, Xiao; Liu, Li; et al.
Abstract: Psychiatric disorders are a group of complex psychological syndromes with high prevalence. It has been reported that gut microbiota has a dominant influence on the risks of psychiatric disorders through gut microbiota–brain axis. We extended the classic gene set enrichment analysis (GSEA) approach to detect the association between gut microbiota and complex diseases using published genome-wide association study (GWAS) and GWAS of gut microbiota summary data. We applied our approach to real GWAS data sets of five psychiatric disorders, including attention deficiency/hyperactive disorder (ADHD), autism spectrum disorder (AUT), bipolar disorder (BD), schizophrenia (SCZ) and major depressive disorder (MDD). To evaluate the performance of our approach, we also tested the genetic correlations of obesity and type 2 diabetes with gut microbiota. We identified several significant associations between psychiatric disorders and gut microbiota, such as ADHD and genus Desulfovibrio ( P = 0.031), order Clostridiales ( P = 0.034). For AUT, association signals were observed for genera Bacteroides ( P = 0.012) and Desulfovibrio ( P = 0.033). Genus Desulfovibrio ( P = 0.005) appeared to be associated with BD. For MDD, association signals were observed for genus Desulfovibrio ( P = 0.003), order Clostridiales ( P = 0.004), family Lachnospiraceae ( P = 0.007) and genus Bacteroides ( P = 0.007). Genus Desulfovibrio ( P = 0.012) and genus Bacteroides ( P = 0.038) appeared to be associated with SCZ. Our study results provide novel clues for revealing the roles of gut microbiota in psychiatric disorders. This study also illustrated the good performance of GSEA approach for exploring the relationships between gut microbiota and complex diseases.